Transmucosal Delivery of Tocotrienols From a Delta-Tocotrienol Powder: A Multidose Pharmacokinetic Study. (14th June 2022) - Moon, Jordan; Gillespie, Jonathan; Wallace, William; Hodges, Falyn; McCoun, Julie; Raub, Betsy; Serrano, Eric
Abstract: Objectives: The purpose of this study was to investigate the pharmacokinetics and bioavailability of a powdered, transmucosal-delivered form of DT3, in healthy men and women. We hypothesized that the larger dose would result in a more-rapid increase and overall greater plasma concentrations of DT3 over time when compared to a lower dose. Methods: Volunteers (m = 8, f = 8, 32 +/− 8 years, 171 +/− 7 cm, 81.6 +/− 13.8 kg) were randomly administered either 40 mg or 80 mg of a DT3-containing powder in a fasted state. Volunteers were asked to keep the powder under their tongue until it was fully dissolved. Two separate doses of 40 mg were given consecutively for the 80 mg group. Blood samples were taken at 0, 60, 90, 120, 180, 240, 360, and 480 minutes. Volunteers were given a meal consisting of carbohydrates, proteins, and fats after four hours. Blood samples collected were placed in a centrifuge to separate blood from plasma. Plasma was collected and stored in a −80°C freezer. DT3 concentrations were calculated from plasma using protein precipitation followed by liquid-liquid extraction. Analytes were separated by HPLC with the extracts assayed against a calibration curve. DT3 bioavailability was assessed using the parameters peak plasma concentration (Cmax ), time to reach peak plasma concentration (Tmax ) and total area under the plasma concentration-time curve (AUC). Results: Plasma concentration of DT3 reached 44.05 ng/ml (Cmax ) for the 40 mg group and reached 127.4 ng/ml (Cmax ) (+97.2% difference) for the 80 mg group. Tmax was achieved at 360 minutes for both the 40 and 80 mg group. AUC for 40 mg resulted in 9, 941.6 ng/ml * min, with a 98.1% increase observed in the 80 mg group (29, 072.2 ng/ml * min). Conclusions: Transmucosal delivery of tocotrienols from a delta-tocotrienol powder containing 40 mg and 80 mg of DT3 resulted in a progressively elevated absorption rate for both doses with 80 mg appearing to increase total plasma DT3 by a difference of +98.1%. Both 40 and 80 mg doses of DT3 administered via transmucosal delivery may enhance plasma DT3 concentrations in healthy men and women over a period of no less than 8 hours. Funding Sources: Support provided by VGI Health Technology Limited.